122k views
11 votes
Simplify sqrt72 -3sqrt12 + sqrt 192

User Mark Ni
by
4.9k points

2 Answers

4 votes

Answer:


6√(2)+2{\sqrt3}

Explanation:

Given expression:


√(72)-3√(12)+√(192)

Rewrite 72 as (36 · 2), 12 as (4 · 3), and 192 as (64 · 3):


\implies √(36 \cdot 2)-3√(4 \cdot 3)+√(64 \cdot 3)

Apply the radical rule
√(a \cdot b)=√(a)√(b) :


\implies √(36)√(2)-3√(4)√(3)+√(64){\sqrt3}

Rewrite 36 as 6², 4 as 2², and 64 as 8²:


\implies √(6^2)√(2)-3√(2^2)√(3)+√(8^2){\sqrt3}

Apply the radical rule
√(a^2)=a :


\implies 6√(2)-3\cdot 2√(3)+8{\sqrt3}

Simplify:


\implies 6√(2)-6√(3)+8{\sqrt3}


\implies 6√(2)+2{\sqrt3}

User Quentin Geissmann
by
5.8k points
9 votes

Answer:

6√2+2√3

Explanation:

We want to simplify the following radical expression


\displaystyle √(72) - 3 √(12) + √(192)

Recall that


√(ab) = √(a) √(b) , \forall \text{a and b such that a$\geq$0,b$\geq$0}

Utilizing the formula yields,


√(72) \implies √(36 \cdot 2) \implies 6 √(2)


√(12) \implies √(4\cdot 3) \implies 2 √(3)


√(192) \implies √(64\cdot 3) \implies 8 √(3)

So,


6 √(2)-3\cdot2 √(3)+8 √(3)

Carry out multiplication:


\implies 6 √(2)-6 √(3)+8 √(3)

Add the like terms:


\boxed{6 √(2)+2 √(3)}

and we're done!

User Vishnu Prasad V
by
5.1k points